International students' satisfaction perception of administrative services: The case of a Turkish university - ciftci, Leyla; Öktem, M. Kemal (Journal of International Students, 2024)
This study examines the perception of international students regarding their satisfaction with administrative services while studying in Türkiye. Internationalization stands as a pivotal policy within Türkiye's higher education framework. In addition to the services students receive at the academic level, the quality of administrative services significantly influences overall student satisfaction. Understanding student satisfaction with public services from their application process to their departure is crucial for identifying and addressing any existing issues. In this context, a survey was conducted with 250 international students at Bartın University. The results indicated general satisfaction with administrative services among participants, with notable variations in responses based on gender, age, prior experiences with administrative issues, and the presence of close relatives or acquaintances in Türkiye. In addition, interviews revealed that the primary causes of administrative difficulties stem from language barriers, procedural complexities in documentation, and associated costs.